Examining the promise of ‘the local’ for improving gender equality in agriculture and climate change adaptation - Acosta, Mariola; Wessel, Margit van; Bommel, Severine van; Feindt, Peter (Informa UK Limited, 2021)
Building on the conceptualisation of ‘the local’ in gender and development discourse, we explore how national and sub-national policy actors in Uganda perceive gender equality policy in the context of agriculture and climate change, to assess the potential of localised solutions to achieve gender equality. Using data from national and sub-national policy actors in Uganda (37 semi-structured interviews, 78 questionnaires), the study found that policy actors largely adhered to global gender discourses in proposing context-specific solutions to gender inequality. Our results show that although local actors identified local norms and culture as major barriers to gender equality, their proposed solutions did not address local gender norms, focussed on formal policy and did little to address underlying causes of gender inequalities. Based on the findings, we suggest that ‘the local’ should be reconstructed as a deliberative space where a wide variety of actors, including local feminist organisations, critically engage, assess and address local gender inequality patterns in agriculture and climate change adaptation processes.